Deconstructing construction wastes: Exploring waste generation causes and their impact on project performances - Usman Aftab; Mughees Aslam; Aman Ulhaq; Farrokh Jaleel; Sohail Malik; Hafiz Zahoor (PLoS ONE, 2025)
The construction industry has long been struggling with excessive costs, delays, and compromised quality due to wasteful practices, particularly in developing nations. While international efforts have focused on identifying waste-related factors, there’s a research gap in pinpointing micro-level causes and analyzing their specific impacts on cost, quality, and time. This study delves into the prevalent and crucial causes of construction waste in Pakistan, evaluating their collective influence on project cost, schedule, quality, and material management. A mix of literature study findings, on-site inspections, and a survey from industry experts was used to determine the causes of non-value-adding/waste generation in construction. Using two rounds of questionnaire survey, 65 valid responses (48% of response rate) were obtained. Following the initial round, the most significant causes and their consequences on waste-related features were identified using the Relative Importance Index (RII) and mean value indexing. To confirm the influence of these waste-generating causes on Pakistani construction projects, assessments from 21 industrial experts were conducted in the second round. The data alignment between the two phases confirmed the impact of the indicated causes on waste. The study determined that inadequate worker training and awareness, planning long duration leading to material escalation, and poor workmanship are the main causes of construction waste in Pakistan. Insights from 21 construction industry experts were also acquired, offering helpful strategies to cut waste in these projects. The outcome of this study clarifies the main reasons for the negative effects of construction waste on the sector and offers recommendations for future steps to reduce their frequency.